Ballistic tests of lightweight hybrid composites for body armor - Yanen, Cenk; Solmaz, Murat Yavuz (Carl Hanser Verlag, 2019)
In the research for this contribution, the use of layered hybrid composites as materials for ballistic armor has been tested. As part of the study, ballistic tests of glass/aramid/carbon fiber laminated comp osite plates at different reinforcing angles, in various numbers and thicknesses were carried out and the results analyzed. Eight hybrid composite laminates, of various thicknesses 200 x 200 mm in size were produced by the hand lay-up method at angles of 0 degrees, +/-45 degrees. Plain and twill fabrics were used to analyze the ballistic performances at various fiber reinforcing angles. Ballistic tests were carried out at the Elazig Special Operation Branch Office, using a Beretta gun loaded with 9 mm FMJ (full metal jacket) bullets. These experiments with ballistic test equipment were conducted in accordance with international standards. During the ballistic experiments, the velocity and BPS (backface signature) was measured and evaluated. Test results suggest that five samples were successful according to NU 0101-06 standards. It was found that twill woven (TW) fabrics made for the study manifest a higher ballistic performance than plain-woven (PW) fabrics. UI) (unidirectional), +/-45 degrees UD fabrics were found to be more effective than 0 degrees UD fabrics. The findings are indicative for the design of lightweight ballistic armor material.
Keywords: Armor material; ballistic performance; hybrid composite